1988
DOI: 10.1037/0278-6133.7.5.387
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and beliefs regarding the consequences of cigarette smoking and their relationships to smoking status in a biracial sample.

Abstract: The purpose of this investigation was to evaluate carefully smoking-related knowledge and beliefs and their relationships to smoking status in a large, heterogeneous sample of smokers and nonsmokers in two settings: (a) a large, biracial southern city and (b) a small midwestern community. Participants were 611 (198 male, 413 female) adult respondents to a random-dialing telephone survey in Fargo, North Dakota (n = 200), and Memphis, Tennessee (n = 411). Each participant was given the Smoking Attitudes Survey, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
51
2

Year Published

1993
1993
2010
2010

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(62 citation statements)
references
References 8 publications
9
51
2
Order By: Relevance
“…Current smokers tend to minimize the health risks of cigarette smoking, and were much more likely to disagree that quitting smoking decreases the risk of lung cancer. Similar results have been reported from several studies in Europe and the United States, and the majority of current smokers underestimate the risk of smokingrelated conditions, such as cancer and heart diseases (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29). Therefore, it is important that women need to learn that quitting smoking lowers their lung cancer risk, as compared with women who continue to smoke.…”
Section: Discussionsupporting
confidence: 64%
“…Current smokers tend to minimize the health risks of cigarette smoking, and were much more likely to disagree that quitting smoking decreases the risk of lung cancer. Similar results have been reported from several studies in Europe and the United States, and the majority of current smokers underestimate the risk of smokingrelated conditions, such as cancer and heart diseases (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29). Therefore, it is important that women need to learn that quitting smoking lowers their lung cancer risk, as compared with women who continue to smoke.…”
Section: Discussionsupporting
confidence: 64%
“…Smoking for weight control has been associated with several variables including younger age, greater nicotine dependence, restrained eating (i.e., restricting eating in order to lose weight or prevent weight gain), and lower levels of self-efficacy to manage weight (Pinto et al, 1999). Although weight concern has been found to be a disincentive to cessation in several cross-sectional studies (Fletcher & Doll, 1969;Klesges, Somes et al, 1988;Loken, 1982;Ogden & Fox, 1994;Streater, Sargent, & Ward, 1989;Weekly, Klesges, & Reylea, 1992), prospective studies have yielded mixed results (French, Jeffery, Klesges, & Forster, 1995;Meyers et al, 1997;French et al, 1995;French, Jeffery, Pirie, & McBride, 1992;Jeffery, Boles, Strycker, & Glasgow, 1997;Jeffery, Hennrikus, Lando, Murray, & Liu, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Klesges et al (1988) found that smokers were more concerned about the health consequences of cholesterol and weight control than non-smokers. However, Castro et al (1989) found no differences between smokers and non-smokers knowledge about stress, diet and smoking.…”
Section: Hypothesis Twomentioning
confidence: 99%
“…t~I • Klesges et al (1988) studied 611 males and females and found that predictors of knowledge about the' health consequence of smoking included:…”
Section: Smokingmentioning
confidence: 99%